The toxicity of liquid supplements containing urea - Bartley, E.E. (Kansas State University. Agricultural Experiment Station, 2011)
Liquid supplement manufacturers must provide a product that is effectively utilized and is nontoxic. Toxicity can be reduced if the supplement's pH is below 3.8, but low pH alone does not improve nutritive value. A good fermentable source of carbohydrate, like molasses or cooked starch, should be provided in adequate amount. When water or lignin sulfonates are substituted for good carbohydrate, urea utilization is reduced and the risk of toxicity is increased. Cattle that are hungry or starved from blizzard conditions or feed restriction are much more susceptible to ammonia toxicity than cattle kept full, so limit the availability of liquid supplements to hungry cattle. Urea is safer if cattle are adapted to it. Always start cattle on urea-containing feeds slowly and keep them full of other feed.
Keywords: Beef; Toxicity; Urea; Liquid supplements